High prevalence of antibiotic-resistant Escherichia coli in Congolese students. (February 2021) - Mfoutou Mapanguy, Claujens Chastel; Adedoja, Ayodele; Kecka, Leissie Graciela Vittickat; Vouvoungui, Jeannhey Christevy; Nguimbi, Etienne; Velavan, Thirumalaisamy P.; Ntoumi, Francine
Highlights: Antimicrobial resistance is of growing concern in sub-Saharan Africa. There is a lack of real-time data recording, surveillance, and regulation in Central Africa. A high prevalence of antibiotic-resistant commensal Escherichia coli was found among Congolese students. Risk factors associated with increased resistance to antibiotics were investigated. Abstract: Background: Antimicrobial resistance (AMR) is of growing concern worldwide, and the AMR status in sub-Saharan Africa (SSA), including the Republic of the Congo, is largely undetermined due to a lack of real-time monitoring. As the incidence of multi-resistant Escherichia coli has been increasing in recent years, an investigation was performed to determine the antibiotic resistance of E. coli isolated from stool samples of Congolese students. Furthermore, factors associated with the carriage of resistant bacteria were investigated. Methods: A total of 339 stool samples from 339 high school students living in the Madibou area of Brazzaville, Republic of Congo, were tested for E. coli . Isolates obtained were tested for susceptibility to 10 antibiotics that are widely used in the region. Results: One hundred and seventy-three (51%) individuals were E. coli -positive in stool, with 61% being female students. Antimicrobial resistance was highest for ceftazidime (65%), followed by amoxicillin (57%), piperacillin–tazobactam (51%), ofloxacin (11%), azithromycin (8%), ciprofloxacin (4%), nalidixic acid (2%), and amoxicillin–clavulanic acid (1%). Antibiotic procurement from non-legalized local vendors had a significant impact on E. coli positivity and antibiotic resistance when compared to procurement from state-licensed pharmacies ( p < 0.05). Conclusions: The high prevalence of resistant commensal E. coli in the community justifies further investigation and urges the need for routine monitoring of antimicrobial susceptibility testing in the region.